2011
DOI: 10.1590/s0004-27492011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Alterações oculares e eletrorretinográficas na doença falciforme

Abstract: INTRODUÇÃODentre as anemias hemolíticas crônicas, a doença falciforme é a mais frequente e incapacitante em nosso meio. Aproximadamente 0,3% a 3% dos nascidos vivos no Estado do Rio de Janeiro, apresentam anemia falciforme e traço falcêmico, respectivamente (1) ; cerca de 0,3% das crianças negras nos Estados Unidos são homozigotos SS (2) . A anemia falciforme é caracterizada pela produção de hemoglobinas anormais que deformam e tornam rígidas as hemácias, causando o aumento da viscosidade sanguínea e oclusão d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Previous studies have shown the importance of ophthalmic evaluations in patients with SCA in order to prevent advanced eye disorders 23 . Cardiomegaly, myocardial ischemia, biventricular dysfunction and pulmonary hypertension are the most frequent clinical complications related to cardiovascular changes in sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the importance of ophthalmic evaluations in patients with SCA in order to prevent advanced eye disorders 23 . Cardiomegaly, myocardial ischemia, biventricular dysfunction and pulmonary hypertension are the most frequent clinical complications related to cardiovascular changes in sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…12 Maculopathy occurs as a result of chronic changes in the perifoveal capillary network. 8 According to David et al, 1 there was macular change in 14.4% of the patients. However, Clarkson found 4.6% of this same type of lesion.…”
Section: Ocular Manifestationsmentioning
confidence: 98%
“…5,7,12 Retinal changes characterize sickle cell retinopathy, which may be non-proliferative or proliferative and is divided into five stages. 1,10,12,13 Among the forms of sickle cell anemia, SS patients present a more severe systemic clinical picture than those with type SC. On the other hand, occlusive ocular effects are more predominant in SC patients, who present only moderate anemia and higher blood viscosity.…”
Section: Ocular Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations